CODE MIXING IN WRITING OPINION ON MEDIA INDONESIA NEWSPAPER - Laude Firima (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
ABSTRACTIn comuniction and social interaction process appear a speaker to use language variation, like: code switching and code mixing. This research only focused in code mixing. Code-mixing was mixing foreign language elements in to the structure of main language. The purpose of this research was to describe the form, background and function of the use of code-mixing in the opinion writing of Media Indonesia News paper. This study used qualitative research. Based on the data analysis, obtainsed descriptions of the use of code mixing form of phrases, words, baster and clauses, description of the background of code- mixing that used outer code- mixing ie. ie using English. The description of the use of code- mixing which serves to identify the role, identification of diversity, and the desire to explain and interpret.Keyword : code mixing, writing opinion, news paper.